Review and Analysis of the ‘Arab Intellect’ from the Perspective of Muhammad Àbid al-Jabiri - Seyyed Mohsen Miri (حکمت اسرا, 2010)
Amongst Muslim thinkers the history and trend of putting forth new and novel models of intellectuality extends back to more than a century ago. The purpose being to restore the necessary capabilities to the Muslim community at large by making amends for past mistakes and backwardness, and to instigate progress and creativity in, amongst others, the scientific, cultural, technological,  and social arenas. Certainly one, if not the most prominent, amongst these theoreticians is the Moroccan intellectual MuÎammad ÝÀbid al-JÁbirÐ. Taking into consideration the fact that the ‘intellect’ and ‘intellectuality’ that appears in the said models is, on the one hand, taken in its modern sense which is completely different from its usual denotation in the past, and on the other, it is used as an instrument for the purpose of resolving contemporary crises and for the sake of progress, it seems necessary that the subject should be tabled in discussions within the realm of Islamic studies and that it should be appraised from the perspective of Islamic philosophy, especially Transcendental Philosophy. In the present study, the views of al-JÁbirÐ with respect to the backwardness of the Arab peoples will be presented, analysed and critiqued.